17PGenomic profiling of non-oncogene-addicted aNSCLC using liquid biopsy. A single institution Italian experience. (7th November 2019) - Di Liello, R; Viscardi, G; Sparano, F; Della Corte, C M; Iacovino, M L; Paragliola, F; Famiglietti, V; Di Liello, A; Ciardiello, F; Morgillo, F
Abstract: Background: cfDNA analysis could represent an alternative to invasive biopsy in patients with NSCLC to better understand disease profile. We report a real-world experience of genomic assessment of an Italian patients' cohort. Methods: We evaluated 58 non-oncogene-addicted aNSCLC patients treated at our Institution from January 2018 to May 2019. All patients were characterized using cfDNA NGS Guardant360® platform (Guardant Health, Redwood City, CA). Association between a positive result (defined as cfDNA detected) and clinical features was assessed using logistic regression test. Using online library dataset (mycancergenome.org) and literature data, we divided patients in genomic clusters and performed a descriptive analysis. Results: The median age of patients was 67 (range 38-85), 44 men and 14 women, 8.6% never smokers, 41.4% former and 50% current smokers. 14 patients (24.2%) had squamous cell carcinoma and 44 (75.8%) had non-squamous NSCLC, 50 of 58 at stage IV at the time of testing. Most patients were PS 0-1 per ECOG scale and has been treated with at least one systemic regimen before performing NGS. 47 of 58 patients (81%) has been considered positive at the analysis. No targetable genomic alterations per local authority has been found. More than 40 different mutated genes were detected, the most common alterations involved TP53 (60% of patients), KRAS (34%), PDGFRα (17%), EGFR (15% - not-TKI-sensitive), PI3KCA (15%), CDKN2A (15%). Chemotherapy (but not immunotherapy) and extra-thoracic radiotherapy before testing increased the probability to result positive at NGS of 4.5 and 2 folds respectively. Six mutational clusters have been identified. Most patients had genomic alterations in Replication Stress - DNA damage/repair, cell cycle - (72%) and Tyrosine Kinase Receptor/Growth Factor pathway (62%), less common mutations affected PI3K/AKT/mTOR and Hormone signaling (26% and 9% respectively). Conclusions: Our experience demonstrated the feasibility of NGS-based NSCLC patients genomic profiling. The widespread of NGS platforms (and the subsequent reduction of costs) should encourage clinicians to use these methods with all patients to guarantee access to developing therapeutics and clinical trials. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: F. Ciardiello: Advisory / Consultancy, Research grant / Funding (institution): Roche; Advisory / Consultancy, Research grant / Funding (institution): Amgen; Advisory / Consultancy, Research grant / Funding (institution): Merck; Research grant / Funding (institution): AstraZeneca; Research grant / Funding (institution): Ipsen; Advisory / Consultancy, Research grant / Funding (institution): Bayer; Advisory / Consultancy: BMS; Advisory / Consultancy: Sanofi; Advisory / Consultancy: Servier; Advisory / Consultancy: Celgene; Advisory / Consultancy: Lilly; Advisory / Consultancy: Pfizer. F. Morgillo: Advisory / Consultancy: MSD; Advisory / Consultancy: Lilly; Research grant / Funding (institution): AstraZeneca. All other authors have declared no conflicts of interest.